PERANAN ORGANISASI NOTARIS DALAM MENEGAKKAN KODE ETIK NOTARIS DI KOTA YOGYAKARTA - , DWI ESKA KENDEDI ADHA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The researcher about the role of notary organizations decide notary code ethic in Yogyakarta with the objective of identifying practices and enforeement of code ethic by notary organizations and finishing or law effect of violation of notary code ethic by notary organizations in Yogyakarta. The researcher method using in this researcher is doing by research through literature data sources, legislation, organizational decisions and conduct interviews with sources related to the writing of this response to the respondents directly related to violations of notari code ethic . beside that from the experience gained during the researcher became Executive Secretary of the Indonesian Notaries Association (I.N.I) and the Association of Official Author Deed Land (I.P.P.A.T) Regional Board of Yogyakarta interrelationships with science writer who gained on the bench lectures at the University of Gadjah Mada University Master of Notary. By doing this research on the writing of research results obtained as follows: 1. Practice code of ethics enforcement in Yogyakarta notary is still limited to the fairness, violations committed by the notary, the notary who is technically still attached and has been repaired. 2. Settlement or the result of violations committed by law-notary its has made a verbal reprimand in meeting of members has also been given a written reprimand related offenses committed by a notary public by the Regional Board of Yogyakarta Indonesian Notaries Association. In this paper the researcher give advice that more attention to the provisions of the notary office to avoid violations, especially on notary code ethic and position of notary.